Characterisation of a bundling protein involved in the self-assembly of bioelastomeric snail egg cases - Loke, Jun Jie (2017)
The carnivorous marine snail Pugilina cochlidium is found predominantly on the sea shores of the South-East Asia region. This sea creature lays a string of egg capsules up to a metre in length which houses its embryos. The egg capsule material must be able to withstand and resist the harsh and relentless tidal forces of the ocean in order for the off-springs to develop properly and survive. The egg capsule was found to be made up of egg capsule protein precursors which domains are predominately filamentous made of coiled-coils. Four laminar protein sheets were also found to be oriented perpendicular to each other. Mechanical testing of the egg capsule had shown that the biomaterial is capable of absorbing shock, where it fully extends upon stretching and is able to recover to its original shape almost instantaneously without significant damage. Investigations of the egg capsule precursor proteins hierarchical native state were carried out using different electrophoresis techniques. This allows a relative comparison of the molecular weight of cross-linked egg capsule protein at different stages in the egg laying process, and how the egg capsule protein precursor might selfassemble prior to secretion. The proteins self-assemble into 200 kDa bundles which are further assembled into fibres with a protein cross-linker, presumably the Pugilina Bundling Protein. Pugilina cochlidium Egg Capsule Protein 1, 2 and 3 were found to be forming the 200 kDa bundles but not for Protein 4 and 5. The genetic sequence of Pugilina Bundling Protein was transformed into the E. coli recombinant system and expressed using Terrific broth to maximise its yield. Protein purification of the solubilised inclusion bodies was carried out using Reversed Phase High Performance Liquid Chromatography. Electrophoresis and Matrix Assisted Laser Desorption/Ionisation Time-of-Flight gave novel insights into the protein ability to form homo-dimers and oligomers. The purified Pugilina Bundling Protein was refolded with L-Arginine as an aggregate suppressor while cysteine/cystine redox pair aided in the proper reshuffling of disulphide bonds. The refolded protein formed dispersed aggregates when mixed with native egg capsule proteins, suggesting that it is partly responsible for the egg capsule hierarchical assembly and cross-linking.